Developing Globally Competitive and Inclusive Higher Education in India - Varghese, N. V. (International Higher Education, 2020)
The massification of higher education is a global phenomenon in this century. The market-led massification of higher education in India is accompanied by widening regional and economic inequalities and persisting social and gender inequalities. An inclusive approach and friendly strategies to provide quality higher education, enhance employability, and improve the global competitiveness of graduates are nonnegotiable elements on the agenda of higher education development.